Two paths to prosperity: Culture and institutions in Europe and China, 1000-2000 - Greif, Avner; Mokyr, Joel; Tabellini, Guido (New Jersey Princeton University Press, 2025)
In the eleventh century, when Europe was still backward and poor, China was a rich and sophisticated civilization. Yet Europe became the birthplace of democracy and the Industrial Revolution, driving the Great Enrichment, while China stagnated until the end of the twentieth century and was always ruled by autocracies. Two Paths to Prosperity traces the emergence of two very different social organizations in premodern China and Europe$1 (Bthe clan and the corporation$1 (Bshowing how they were key factors in the economic and political divergence of these two great civilizations.s